2018
DOI: 10.1155/2018/1241323
|View full text |Cite
|
Sign up to set email alerts
|

IFNα-Expressing Amniotic Fluid-Derived Mesenchymal Stem Cells Migrate to and Suppress HeLa Cell-Derived Tumors in a Mouse Model

Abstract: Background Immunotherapy for cervical cancer with type I interferon (IFN) is limited because of the cytotoxicity that accompanies the high doses that are administered. In this study, we investigated the utilization of amniotic fluid-derived mesenchymal stem cells (AF-MSCs) as a means for delivering IFNα to local tumor sites for the suppression of cervical cancer in a mouse model using HeLa cell xenografts. Methods The tumor tropism ability of AF-MSCs and AF-MSCs genetically modified to overexpress IFNα (IFNα-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Increasing attention has been paid to research on immunotherapy for cervical cancer. Zhou J et al have shown that IFNα-expressing amniotic fluid-derived mesenchymal stem cells can suppress HeLa cell-derived tumors in a mouse model [ 6 ]. An HPV vaccine containing some HPV16 E7 peptides presents an anti-tumor effect in tumor-free mice [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing attention has been paid to research on immunotherapy for cervical cancer. Zhou J et al have shown that IFNα-expressing amniotic fluid-derived mesenchymal stem cells can suppress HeLa cell-derived tumors in a mouse model [ 6 ]. An HPV vaccine containing some HPV16 E7 peptides presents an anti-tumor effect in tumor-free mice [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the cells attached to the upper side of the membrane were removed and the migrated cells on the lower side were stained with trypan blue and counted under an inverted microscope (five fields of view, at 10× magnification). Experiments were done in triplicate 20 …”
Section: Methodsmentioning
confidence: 99%
“…When B16F0 tumors were established, the labeled cells were injected into the mice tail vein. At different times post‐injection (up to 5 days), fluorescent imaging of isolated organs and tumors was performed using Kodak in vivo imaging system F Pro (CRI, Inc., Woburn, MA) 20,21 …”
Section: Methodsmentioning
confidence: 99%
“…Mouse models are critical tools in preclinical and translational research in hepatopancreatobiliary cancer [ 1 ], including drug screening, assessment of therapeutic efficacy, identification of biomarkers, and molecular subtyping. Traditionally, immortalized cancer cell lines derived from patient tumours are used to construct mouse models to simulate tumour growth in the human body [ 2 ]. In these models, immortalized cancer cell lines are injected into immunodeficient mice subcutaneously or orthotopically [ 3 ].…”
Section: Introductionmentioning
confidence: 99%